1995
DOI: 10.1007/bf03349817
|View full text |Cite
|
Sign up to set email alerts
|

Solitary skin metastasis as the presenting feature of differentiated thyroid microcarcinoma: Report of two cases

Abstract: Cutaneous metastases from thyroid neoplasia are very rare. Most patients presenting with such a disease have also both internal metastases and a very enlarged thyroid gland. We reported here 2 patients presenting with differentiated thyroid microcarcinoma which was revealed by a solitary scalp lesion. The positive immunoperoxidase staining for thyroglobulin (TG) in the skin tumour cells asserted the diagnosis of metastatic thyroid carcinoma. The thyroid neoplastic micronodular formation was unrecognized by ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 16 publications
1
39
0
2
Order By: Relevance
“…[16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions. The thyroid lesions of 0.4 and 0.5 cm size in the cases were unrecognized by ultrasonography and they were only detected at serial histological examination of thyroid glands removed during surgery.…”
Section: Follicular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Eighteen cases of FTC metastasis to scalp were reported in the literature [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table 1). Two cases reported by Lissak et al [20] were follicular microcarcinoma revealed by solitary scalp lesions. The thyroid lesions of 0.4 and 0.5 cm size in the cases were unrecognized by ultrasonography and they were only detected at serial histological examination of thyroid glands removed during surgery.…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…The presenting symptom was a scalp lesion in 7 cases. [3,17,[20][21][22] Metastases to scalp 1 to 18 years after the diagnosis of the primary FTC were reported in the literature (Table 1).…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…Cutaneous metastases of these types of carcinomas are rarely seen, except in the vicinity of a locally invasive tumor. Skin metastases confirmed by immunohistochemistry have been reported in seven cases of follicular carcinoma (1)(2)(3)(4)(5) and in six cases of papillary carcinoma (5)(6)(7)(8), two of which were of the follicular variant type (5,6). Metastases from follicular carcinomas were located in the scalp (1,(3)(4)(5), neck (1) and cheek (2).…”
Section: Introductionmentioning
confidence: 98%
“…Skin metastases confirmed by immunohistochemistry have been reported in seven cases of follicular carcinoma (1)(2)(3)(4)(5) and in six cases of papillary carcinoma (5)(6)(7)(8), two of which were of the follicular variant type (5,6). Metastases from follicular carcinomas were located in the scalp (1,(3)(4)(5), neck (1) and cheek (2). In five cases of papillary carcinoma, skin metastases were located only in the scalp (5)(6)(7)(8), and in one case there were multiple sites of dissemination, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation